Komunikasi Interpersonal dalam Perkuliahan Daring Fakultas Komunikasi dan Bahasa Universitas BSI - Rety Palupi; Gema Irhamdhika (LPPM UBSI, 2022)
With the outbreak of the Covid-19 case in 2020 in Indonesia, the Minister for Administrative Reform and Bureaucratic Reform (PAN & RB) made adjustments to the Work System of the State Civil Apparatus (ASN) in Efforts to Prevent the Spread of the Covid-19 Virus in Government Area. In this policy, it will affect all lines of society in carrying out daily activities. It is undeniable that this policy has an impact on the education sector in Indonesia. The policy implemented is the holding of learning activities through the network (online) ranging from students to teachers due to social restrictions. The Minister of Education and Culture of the Republic of Indonesia issued Circular No. 4 of 2020 on the second point regarding the Implementation of Educational Policies during the Covid-19 Pandemic. But in practice there are some parties who may try to adapt to this new habit. Especially in the online teaching and learning process. Hereby the author raises about the effectiveness of Interpesona communication in the implementation of online lectures at the Faculty of Communication and Language, Bina Sarana Informatika University. The theories used in this research are interpersonal communication, digital communication, and new media. The research method used in this research is descriptive and explanatory method with a quantitative approach. After getting data from the results of the grouping of scores, it can be concluded that the respondents assessed that interpersonal communication occurred and was carried out effectively during online lectures during the Covid-19 pandemic.